Sui "virelais" di Guillaume de Machaut (con una nuova edizione di «Douce dame jolie») (Carte Romanze, 2024)
In this article we study the genre of virelai in Guillaume de Machaut, maintaining the idiographic manuscript tradition of the well-known author at the center of the analysis.